2021
DOI: 10.1177/02692163211040186
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and measures of delirium interventional studies in palliative care to inform a core outcome set: A systematic review

Abstract: Background: Trials of interventions for delirium in various patient populations report disparate outcomes and measures but little is known about those used in palliative care trials. A core outcome set promotes consistency of outcome selection and measurement. Aim: To inform core outcome set development by examining outcomes, their definitions, measures and time-points in published palliative care studies of delirium prevention or treatment delirium interventions. Design: Prospectively registered systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Thorough guidelines, statements, and core outcome sets for delirium have previously been produced using consensus methods 13 19–30 . For example, the Network for Investigation of Delirium: Unifying Scientists (NIDUS) 2020 Scientific Think Tank listed identifying etiologic subtypes of delirium as a priority 31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorough guidelines, statements, and core outcome sets for delirium have previously been produced using consensus methods 13 19–30 . For example, the Network for Investigation of Delirium: Unifying Scientists (NIDUS) 2020 Scientific Think Tank listed identifying etiologic subtypes of delirium as a priority 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Thorough guidelines, statements, and core outcome sets for delirium have previously been produced using consensus methods. 13 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 For example, the Network for Investigation of Delirium: Unifying Scientists (NIDUS) 2020 Scientific Think Tank listed identifying etiologic subtypes of delirium as a priority. 31 The think tank suggested that future studies should use standardized approaches to identify contributors to delirium, to incorporate biomarkers, and to use subtyping to guide targeted treatments.…”
Section: Introductionmentioning
confidence: 99%